The Mystery of Values Studies in Axiology - Grünberg, Ludwig (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This study of axiology explores the axiocentricity of being human. Human beings dwell in the realm of value. Values are not simply what persons have; values in large part are what persons are. The mystique of values is analyzed here in terms of their cultural, phenomenological, and ontological status. The relationship between science and values is debated. Values should not be submitted to reductionism. Postmodernism raises new problems for the future of a philosophy of values. Yet, we may direct our hopes toward happiness, universalism, and humanism as inseparable from value-life.